Agricultural biotechnology : (National academy press, 1987)
Biotechnology offers tremendous potential for improving crop production, animal agriculture, and bioprocessing. It can provide scientists with new ways to develop higher-yielding and more nutritious crop varieties, to improve resistance to disease, or to reduce the need for inputs of fertilizers and other expensive agricultural chemicals. This book explores the United States' ability to solve important agricultural problems, effectively use funds and institutional structures to support biotechnology research for agriculture, train researchers in new scientific areas, efficiently transfer technology, and regulate and test recombinant DNA organisms in the field.